Development and validation of an integrated mechatronic apparatus for measurement of friction coefficients of agricultural products - S.M. Shafaei; A. Nourmohamadi-Moghadami; S. Kamgar; M. Eghtesad (Information Processing in Agriculture, 2020)
An integrated mechatronic apparatus was developed based on tilting plate method in order to precisely measure static friction coefficient (SFC) and dynamic friction coefficient (DFC) of agricultural products. The apparatus consisted of two main parts (mechanical and electrical parts). The main element of mechanical part was rotary container. Meanwhile, the electrical part included control, display, goniometer, level controller, rotational power supply, and infrared unit. The apparatus was initially simulated in simulation environment and practically calibrated to achieve high precision measurements. To appraise performance of the apparatus, the SFC and DFC of three grains were measured on five contact surfaces. Experiments were also conducted by means of a typical apparatus operating based on puling force method. Some statistical descriptor parameters such as mean absolute percentage error (MAPE), average of absolute values of measurement errors (AAVME), maximum of absolute values of measurement errors (MAVME), and correlation coefficient were used to compare accuracy of the apparatus with the typical one. The acceptable AAVME (<10%), MAVME (<10%), MAPE (<5%), and correlation coefficient (>0.9) indicated high accuracy, stability, and efficiency of the apparatus for automatic measurements of the SFC and DFC. From practical point of view, the mechatronic apparatus would be a beneficial tool for experimental, educational, demonstrational, and research works. Keywords: Static friction coefficient, Dynamic friction coefficient, Physical property, Friction force